Land Conservation Tools and Zoning - Lauren McDonell; Martha C. Monroe; Basil V. Iannone (EDIS)
FOR195, a 3-page illustrated fact sheet by Lauren McDonell and Martha C. Monroe, outlines land conservation tools and the types of zoning that can improve ecological conditions, create recreational opportunities, and reduce human conflicts in the wildland-urban interface. Includes references. Originally published  July 2008 as Land Use in the Wildland-Urban Interface: Land Conservation Tools and Zoning.